2015
DOI: 10.1186/s12936-015-0664-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study to evaluate the clinical safety of the fixed-dose artemisinin-based combination Eurartesim® (dihydroartemisinin/piperaquine), in public health facilities in Burkina Faso, Mozambique, Ghana, and Tanzania

Abstract: BackgroundThe World Health Organization recommends artemisinin-based combination (ACT) for the treatment of uncomplicated malaria. Post-licensure safety data on newly registered ACT is critical for evaluating their risk/benefit profile in malaria endemic countries. The clinical safety of the newly registered combination, Eurartesim®, following its introduction into the public health system in four African countries was assessed.MethodsThis was a prospective, observational, open-label, non-comparative, longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 23 publications
(17 reference statements)
4
40
1
Order By: Relevance
“…For amodiaquine–artesunate, a study with over 15,000 malaria cases in Ivory Coast was required as part of the WHO-approved Risk Management Plan. Dihydroartemisinin (DHA)–piperaquine was linked to an increased QTc (corrected Q-T wave) interval but no further cardiac sequelae ; gathering data from over 16,000 patients [31], and 10,000 patients, including a nested study of 1000 patients with thorough electrocardiogram (ECG) monitoring [32] has been required for this treatment to be accepted for WHO prequalification. Pyronaridine–artesunate (Pyramax ® ) produced an acute, transient and asymptomatic elevation of liver enzyme levels in phase III patients, also seen in healthy Caucasian volunteers after re-dosing.…”
Section: The Single-exposure Cure Dilemma: Efficacy Versus Safety In mentioning
confidence: 99%
“…For amodiaquine–artesunate, a study with over 15,000 malaria cases in Ivory Coast was required as part of the WHO-approved Risk Management Plan. Dihydroartemisinin (DHA)–piperaquine was linked to an increased QTc (corrected Q-T wave) interval but no further cardiac sequelae ; gathering data from over 16,000 patients [31], and 10,000 patients, including a nested study of 1000 patients with thorough electrocardiogram (ECG) monitoring [32] has been required for this treatment to be accepted for WHO prequalification. Pyronaridine–artesunate (Pyramax ® ) produced an acute, transient and asymptomatic elevation of liver enzyme levels in phase III patients, also seen in healthy Caucasian volunteers after re-dosing.…”
Section: The Single-exposure Cure Dilemma: Efficacy Versus Safety In mentioning
confidence: 99%
“…No previous observational CEM study has evaluated the incidence of AEs in patients treated specifically with an identified ASAQ fixed-dose combination tablet, and several previous studies have evaluated different anti-malarial drugs in the same study. The present study is also much larger than previous studies, which included <5000 patients (with the exception of one recent multinational study that also recruited >10,000 patients [21]). In addition, different methods of data collection have been used in these various CEM studies.…”
Section: Discussionmentioning
confidence: 89%
“…Other CEM studies of ACT in Nigeria [25] and of artemether–lumefantrine (Coartem ® ) in Tanzania [26] also required patients to return to the HC or to contact a CHW. The study that is perhaps the closest to the present one in design is the INDEPTH study of a fixed-dose combination of dihydroartemisinin and piperaquine phosphate (Eurartesim ® ), conducted in four African countries between 2013 and 2014 [21], which included 11,097 patients with RDT-confirmed P. falciparum infections who were followed up by home visits from a CHW or by telephone. More recently, a study in Ghana of patients prescribed ACT [27] has compared telephone contact and home visits by a CHW and found that the former method elicited more AEs and was less expensive to implement.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the WHO collaborating centers of excellence in pharmacovigilance in some countries such as Ghana 58 and efforts by the INDEPTH Network, a nongovernmental organization made up of research institutions with health and demographic surveillance systems. 59 The key challenge in Phase IV studies is the lack of baseline disease profiles of rare diseases due to inadequate diagnostic tools in many health facilities in sub-Saharan Africa. As a result, Phase IV malaria vaccine studies to be carried out in subSaharan Africa would require further assessments of some rare diseases reported to be associated with vaccines such as intussusception 60 and Kawasaki Syndrome.…”
Section: Preparations For Phase IV Malaria Vaccine Trialsmentioning
confidence: 99%